A Perspective Study on the Etiology of Diarrhea in Children Less than 12 Years of age attending Kanti Children’s Hospital - Pokharel, M; Sherchand, JB; Upreti, HC; Katuwal, A; Gauchan, P (Journal of Nepal Paediatric Society, 2009)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--> <!--[if gte mso 10]> <![endif]--> Introduction: Diarrhea is the most common illness among children causing highest number of mortality and morbidity in the developing countries. Objective: This study was conducted to determine the etiological agents of diarrhea in children less than 12 years of age. Methods: The study was carried out in Tribhuvan University Teaching Hospital, Health Research Laboratory and stool specimen were collected from Kanti Children's Hospital between February 2007 and August 2007. The specimens were processed by standard microbiological methods, serological diagnosis for the complete identification of bacterial isolate and use of Rotaclone for diagnosis for Rotavirus. Results: A total 500 specimen were processed and 312 (62.4%) cases were identified with enteropathogens. Out of 500, 165 (33%) showed significant bacterial growth, 110 (22%) single or multiple parasitic infestation, and 167 (21.4%) Rotavirus. Among the bacterial isolate, Escherichia. coli (20.2%) were highest in number, Entamoeba. histolytica (10%), among the protozoa and Ascaris lumbricoide (1.4%) among the helminth. Age group 0-2 years showed most number of cases. The prevalence of Rotavirus infection was more in Inpatient (65.4%) than Outpatient (34.6%) (P>0.05). Ethnicgroup wise distribution showed that Gurung/Magar/ Rai/Tamang were highly infected (34.6%) (P>0.05). Conclusion: The results showed that bacteria were the major etiological agents of diarrhea in children than parasites and Rotavirus. E. coli among the bacteria, E. histolytica among the parasite and Rotavirus constituted the major causative agents identified. The age group 0-2years was the most vulnerable group where most of the enteropathogens were detected. Key words: Bacteria, Children Diarrhea, Parasites, Rotavirus doi:10.3126/jnps.v29i1.1594 J. Nepal Paediatr. Soc. Vol.29(1) p.10-16